APLIKASI KONSORSIUM BAKTERI PENAMBAT NITROGEN DAN PELARUT FOSFAT UNTUK MENINGKATKAN PERTUMBUHAN JAGUNG (Zea mays) - Fandi Hidayat; Zulham Sembiring; Elli Afrida; Fuad Balatif (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2020)
Maize (Zea mays) is one of the major crops and widely grown in Indonesia. On average, current maize yields are still below its potential. Thus, it needs to increase by good agricultural practices such as applying biofertilizer, which consists of beneficial bacteria. This research was aimed to find out the impact of the bacterial consortium of nitrogen-fixing bacteria (BPN) and phosphate solubilizing bacteria (BPF) on the maize growth. The study was conducted in the greenhouse and arranged in a completely randomized design (CRD) with treatments, i.e.: (1) negative control (no inorganic fertilizer and BPN-BPF); (2) positive control (100% inorganic fertilizer); (3) only BPN-BPF applied (no inorganic fertilizer); (4) 75% inorganic fertilizer + BPN-BPF; and (5) 50% inorganic fertilizer + BPN-BPF. The results revealed that the consortium of nitrogen-fixing bacteria and phosphate solubilizing bacteria significantly improved certain soil chemical properties, such as C-organic, cation exchange capacity (CEC), and the availability of nitrogen and phosphorus in the soil. Besides, the consortium of BPN and BPF also increased the maize growth and total biomass up to 19%. Further, a consortium of BPN and BPF increased the fertilizer efficiency by reducing the dosage of inorganic fertilizer up to 50%.